2015
DOI: 10.1007/s11150-015-9297-6
|View full text |Cite
|
Sign up to set email alerts
|

Teenagers’ risky health behaviors and time use during the great recession

Abstract: This paper uses individual-level data from both the 2003-2011 American Time Use Survey and Youth Risk Behavior Survey along with state-level unemployment rates to examine the effects of a weakening economy during the Great Recession on U.S. teenagers' activities. Black male teenagers had less sex and spent more time with their parents. Hispanic male teenagers spent less time playing sports and more time watching time TV, and were more likely to be obese. Female teenagers, on the other hand, spent less time wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…These questions are critical as the COVID-19 pandemic spreads worldwide in 2020. Unexpected shocks, such as a great recession, affect modern life and thus, time allocation (e.g., Aguiar et al 2013 ; Gorsuch 2016 ; Pabilonia 2017 ). The government has required people to work from home to contain the spread of COVID-19, which inevitably leads to recession.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These questions are critical as the COVID-19 pandemic spreads worldwide in 2020. Unexpected shocks, such as a great recession, affect modern life and thus, time allocation (e.g., Aguiar et al 2013 ; Gorsuch 2016 ; Pabilonia 2017 ). The government has required people to work from home to contain the spread of COVID-19, which inevitably leads to recession.…”
Section: Introductionmentioning
confidence: 99%
“…However, other than Sevilla and Smith (2020), not many studies have investigated how school closure affects parents' work from home and causes gender differences in work styles during 1 Self-care after school leads to an increased risk of skipping school and use of alcohol and drugs (Aizer 2004). Economic recessions increase teenagers' risky behaviors (Pabilonia 2017). A mother's absence reduces the time a child spends in school (Pörtner 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related, Bassols, et al (2016) showed that the Great Recession increased legal and illegal drug use in Spain. Pabilonia (2015) investigates the impact of the Great Recession on teenagers' risky behaviors in the Youth Risk Behavior Survey and the American Time Use 5 Survey. Argys, et al (2016) show that the run-up of household debt during the Great Recession was accompanied by increased mortality risk.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Unexpected external shocks, such as the Great Recession, were observed to change time allocation in the daily life (e.g. Aguiar et al 2013 ; Gorsuch 2016 ; Pabilonia 2017 ). …”
mentioning
confidence: 99%